2021
DOI: 10.3390/nursrep11030047
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mothers’ Knowledge, Attitudes, and Practices Regarding Childhood Vaccination during the First Five Years of Life in Saudi Arabia

Abstract: Aim: This study’s aim was to assess the knowledge, attitudes, and practices of mothers regarding childhood vaccination during the first five years of children’s lives in Saudi Arabia. Method: A cross-sectional, descriptive study was conducted with the application of convenience sampling, and 262 questionnaires were completed by Saudi mothers who had children aged 5 years or younger. Results: The majority of the participants were aged 25–31 years (57%), 61% held a bachelor’s degree, and 60.3% had children aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 14 publications
(33 reference statements)
7
21
5
Order By: Relevance
“…It was found that the average knowledge score of the respondents in regard to childhood vaccination was good at 7.22±1.30 with an overall correct rate of 80.23%. This finding is similar with the results of two previous studies that were conducted in Saudi Arabia and North East Ethiopia, 31 , 32 which confirmed that respondents have good knowledge of childhood vaccination, know the importance of giving complete vaccinations to their children, and understand that vaccination is not harmful. Another similarity from these studies is the results highlighted positive correlations between parents’ level of education and occupational status with their knowledge.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was found that the average knowledge score of the respondents in regard to childhood vaccination was good at 7.22±1.30 with an overall correct rate of 80.23%. This finding is similar with the results of two previous studies that were conducted in Saudi Arabia and North East Ethiopia, 31 , 32 which confirmed that respondents have good knowledge of childhood vaccination, know the importance of giving complete vaccinations to their children, and understand that vaccination is not harmful. Another similarity from these studies is the results highlighted positive correlations between parents’ level of education and occupational status with their knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…34 , 35 This situation is relevant with the finding of three previous studies, which specifically highlighted that comprehensive information and guideline were still required by respondents who have positive attitudes towards childhood vaccinations. 31 , 32 , 36…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the correlation between KAP levels and the demographics of the moms, mothers over the age of 35 had a significantly greater percentage of good immunization practice. The similar thing was seen in a prior Saudi study, where the mother's age was one of the common characteristics linked to higher knowledge and attitude (Almutairi et al, 2021). The similar result was seen in a research lead in Ethiopia, where there was a connection between knowledge level and mother's age (Ramadan et al, 2016).…”
Section: Resultssupporting
confidence: 82%
“…Parents, in general, and mothers, in particular, can strongly influence childhood vaccination decisions 7 . However, little is known about vaccine hesitancy among pregnant women.…”
Section: Introductionmentioning
confidence: 99%